Pengaruh Edukasi Audiovisual Interaktif Terhadap Pengetahuan Dan Sikap Tentang Menstruasi Normal Pada Remaja Putri Usia 14–16 Tahun: Sebuah Studi Berbasis Sekolah - Ladya Mutiara Firnanda Prasticia; Anik Sri Purwanti; Widia Shofa Ilmiah (Borneo Nursing Journal (BNJ), 2026)
Menstruation is a normal physiological process in adolescent girls; however, knowledge and attitudes toward normal menstruation are often still suboptimal. This study aimed to analyze the effect of interactive audiovisual education on adolescent girls’ knowledge and attitudes regarding normal menstruation at SMK Diponegoro Tumpang. This study employed a pre-experimental one-group pretest-posttest design involving 32 tenth-grade female students selected based on the study criteria. Data were collected using knowledge and attitude questionnaires and analyzed using univariate and bivariate methods. The Shapiro-Wilk normality test indicated that the data were not normally distributed; therefore, differences between pretest and posttest scores were tested using the Wilcoxon Signed-Rank Test. The results showed that the mean knowledge score increased from 2.41 to 2.97, while the mean attitude score increased from 1.25 to 1.31. The Wilcoxon test yielded p = 0.0123 with an effect size of r = 0.44, indicating a statistically significant moderate effect after the intervention. It can be concluded that interactive audiovisual education improves knowledge and supports positive attitude changes among adolescent girls regarding normal menstruation. This intervention may serve as an effective reproductive health promotion medium in schools.